A vajdasági magyarok és az EU - Gábrity Molnár, Irén (Közép-Európai Közlemények, 2009)
Hungarians in Vojvodina are totally aware of their history and thank to their values they represent a European nation. Particularly since the home-land, Hungary is member of the EU, Hungarians in Vojvodina are in a status of waiting. The emigrational willingness of Hungarians in Vojvodina seems to be extreme: the majority of them wish to stay in Serbia, namely in Vojvodina, but there are some who wish to travel to other continents. It is supposable that those who are to remain in Vojvodina are looking forward to becoming an EU member, while those who do not find EU membership to result in economic, social advancement are still considering emigration.